A novel XRF method to measure environmental release of copper and zinc from antifouling paints. (June 2017) - Ytreberg, Erik; Lagerström, Maria; Holmqvist, Albin; Eklund, Britta; Elwing, Hans; Dahlström, Magnus; Dahl, Peter; Dahlström, Mia
Abstract: The release of copper (Cu) and zinc (Zn) from vessels and leisure crafts coated with antifouling paints can pose a threat to water quality in semi-enclosed areas such as harbors and marinas as well as to coastal archipelagos. However, no reliable, practical and low-cost method exists to measure the direct release of metals from antifouling paints. Therefore, the paint industry and regulatory authorities are obliged to use release rate measurements derived from either mathematical models or from laboratory studies. To bridge this gap, we have developed a novel method using a handheld X-Ray Fluorescence spectrometer (XRF) to determine the cumulative release of Cu and Zn from antifouling paints. The results showed a strong linear relationship between XRF Kα net intensities and metal concentrations, as determined by ICP-MS. The release of Cu and Zn were determined for coated panels exposed in harbors located in the Baltic Sea and in Kattegat. The field study showed salinity to have a strong impact on the release of Cu, i.e. the release increased with salinity. Contrary, the effect of salinity on Zn was not as evident. As exemplified in this work, the XRF method also makes it possible to identify the governing parameters to the release of Cu and Zn, e.g. salinity and type of paint formulation. Thus, the XRF method can be used to measure environmentally relevant releases of metallic compounds to design more efficient and optimized antifouling coatings. Graphical abstract: Highlights: A new XRF method to measure release of metals from antifouling paints was developed. The XRF method is fast, non-destructive and accurate. Panels were coated with antifouling paints and exposed in harbors. The field study showed salinity to increase the release of copper. The method can be used in risk assessment to derive in situ releases of biocides. Abstract : A novel release rate method has been developed and used to determine releases of metallic compounds from antifouling paints exposed in the Baltic Sea and Kattegat.